Polyimide-based composite material and preparation method thereof

By performing low-temperature reaction and chemical cyclization treatment in solvents, the melting point of polyimide resin is reduced, the problem of difficult forming of polyimide composite materials is solved, and its fluidity and mechanical properties are improved. It is suitable for aerospace , electrical and automotive industries.

CN119285948AInactive Publication Date: 2025-01-10SHAANXI DAOBO FEIKE NEW MATERIAL TECH CO LTD

Patent Information

Application Number
CN202411698294.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-01-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The high melting point of polyimide-based composites leads to difficult forming, limiting their application in the aerospace, electrical and automotive industries.

Method used

By conducting a low-temperature reaction in a solvent, a polyamic acid solution is formed using aromatic diamine monomers and aromatic dianhydride monomers, and chemical cyclization is carried out to reduce the melting point of the polyimide resin, improve its fluidity and melting sex.

Benefits of technology

The melting point of the composite material has been successfully reduced, the ease of forming and mechanical properties are improved, and the problem of polyimide-based composite materials in the prior art is not easy to melt and have poor fluidity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of composite materials, and particularly discloses a polyimide-based composite material and a preparation method thereof. The polyimide-based composite material is prepared from the following raw materials in parts by weight: 5 to 30 parts of aromatic dianhydride monomer, 4 to 38 parts of aromatic diamine monomer, 1 to 10 parts of end-capping reagent, 5 to 30 parts of acetic anhydride, 3 to 15 parts of triethylamine and 35 to 60 parts of solvent. The preparation method comprises the following steps: carrying out low-temperature reaction on an aromatic diamine monomer and an aromatic dianhydride monomer in a solvent to form a polyamide acid solution, and carrying out chemical cyclization treatment to obtain fusible polyimide; the polyimide resin prepared by the invention is easy to melt and good in fluidity, solves the problems of higher melting point, difficulty in melting and poor fluidity of a polyimide-based composite material in the prior art, and reduces the forming difficulty of the composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite materials, and in particular to a polyimide-based composite material and a preparation method thereof. Background Art

[0002] As a high-temperature resistant composite resin matrix, polyimide has excellent thermal stability, electrical insulation and mechanical properties, and is widely used in aerospace, electrical and automotive industries. The high melting point of polyimide resin makes it difficult to form composite materials, which limits the development and application of polyimide composite materials. Therefore, it is of great significance to develop a polyimide-based composite material that can melt and withstand high temperatures. Summary of the invention

[0003] In order to overcome the deficiencies of the prior art, the present invention provides a polyimide-based composite material on one hand, so as to improve the high temperature resistance of the composite material and reduce its melting point.

[0004] A polyimide-based composite material comprises, by weight, 5-30 parts of aromatic dianhydride monomers, 4-38 parts of aromatic diamine monomers, 1-10 parts of end-capping agents, 5-30 parts of acetic anhydride, 3-15 parts of triethylamine and 35-60 parts of solvents.

[0005] Optionally, the diamine monomer is one or more of 4,4'-diaminodiphenylmethane, m-phenylenediamine, 4,4'-diamino-2,2'-bistrifluoromethylbiphenyl, p-phenylenediamine, 9,9-bis(4-aminophenyl)fluorene or the like.

[0006] Optionally, the aromatic dianhydride monomer is selected from one or more of 1,4,5,8-naphthalenetetracarboxylic anhydride, 3,3',4,4'-biphenyltetracarboxylic anhydride, 2,3,3',4'-biphenyltetracarboxylic anhydride, pyromellitic anhydride, hexafluoroisopropylphthalic anhydride or the like.

[0007] Optionally, the end-capping agent is selected from one or more of 4-phenylethynylphthalic anhydride, 5-norbornene-2,3-dicarboxylic anhydride or the like.

[0008] Optionally, the solvent is one or more of N,N-dimethylformamide, N,N-dimethylacetamide or N-methylpyrrolidone.

[0009] Another aspect of the present invention provides a method for preparing the above-mentioned polyimide-based composite material, comprising the following steps:

[0010] S1, adding a solvent into a three-necked flask, introducing nitrogen into the three-necked flask and continuously stirring, adding a diamine monomer into the solvent and stirring evenly to obtain a first mixed solution;

[0011] S2, adding aromatic dianhydride monomer and end-capping agent to the first mixed solution and stirring evenly to obtain a polyamic acid solution;

[0012] S3, performing imidization treatment on the polyamic acid solution to obtain a second mixed solution;

[0013] S4, precipitating, filtering and drying the second mixed solution to obtain polyimide powder;

[0014] S5, adding the polyimide powder into the ethanol solution and stirring evenly to obtain a polyimide resin solution;

[0015] S6, evenly spreading the polyimide resin solution on the fiber fabric and drying it to obtain a prepreg, and curing the prepreg to obtain a polyimide-based composite material.

[0016] Optionally, the imidization treatment is specifically:

[0017] Add acetic anhydride and triethylamine to the polyamic acid solution, and continue stirring at 20-35° C. for 10-12 hours;

[0018] The solid content of the polyimide resin solution is 10-50%, and the molecular weight of the polyimide is 2200-7500.

[0019] Optionally, the stirring temperature of the solvent is -10-15°C.

[0020] Aromatic diamine monomers and aromatic dianhydride monomers react at low temperature in a solvent, which makes it easy to control the molecular weight of the polyimide resin, improve the solubility of the resin and reduce the melting point of the resin.

[0021] Optionally, the amount of the polyimide resin solution laid is 1.2 times the weight of the fiber fabric;

[0022] The fiber fabric is first baked at 50° C. for 2 hours, and then baked at 70° C. for 6-8 hours to obtain a prepreg;

[0023] The glue content of the prepreg is 30-40%.

[0024] Optionally, the prepreg curing molding is specifically:

[0025] 20 sheets of prepreg were overlapped and laid in the mold and placed in a press at 100°C for 0.5h, then kept at 150°C for 0.5h, and then the mold cover was closed and the press was closed; the temperature was further increased to 240°C for 0.5h, and then to 350°C for 20min, and the press pressure was increased to 2.5MPa;

[0026] Continue to raise the temperature to 370℃ and keep it for 2h, then keep it at 385℃ for 2h to complete the curing.

[0027] The beneficial effects of the present invention are as follows: the present invention forms a polyamic acid solution by reacting an aromatic diamine monomer and an aromatic dianhydride monomer in a solvent at a low temperature, and performs a chemical cyclization treatment to obtain a fusible polyimide; the polyimide resin prepared by the present invention is easy to melt, has good fluidity, and is conducive to molding processing, thereby solving the problems of high melting point, difficulty in melting, and poor fluidity of polyimide-based composite materials in the prior art, and reducing the difficulty of composite material molding. DETAILED DESCRIPTION

[0028] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] The raw material information involved in the present invention is shown in Table 1.

[0030] Table 1 Raw material information

[0031]

[0032]

[0033] Example

[0034] Example 1

[0035] A polyimide-based composite material is prepared by the following steps:

[0036] S1. Add 205 g (2.07 mol) of N-methylpyrrolidone into a three-necked flask equipped with a mechanical stirring device and a nitrogen introduction device, introduce nitrogen into the three-necked flask, and mechanically stir at -10°C. Add 96.07 g (0.3 mol) of 4,4'-diamino-2,2'-bistrifluoromethylbiphenyl into the three-necked flask to uniformly dissolve 4,4'-diamino-2,2'-bistrifluoromethylbiphenyl in N-methylpyrrolidone to obtain a first mixed solution.

[0037] S2, 70.61 g (0.24 mol) of 3,3',4,4'-biphenyltetracarboxylic dianhydride and 29.79 g (0.12 mol) of 4-phenylethynylphthalic anhydride were sequentially added to the first mixed solution, and stirred at 25° C. for 2 h to obtain a polyamic acid solution;

[0038] S3, adding 114 g (1.12 mol) of acetic anhydride and 38 g (0.38 mol) of triethylamine to the polyamic acid solution, stirring at 25° C. for 12 h to obtain a second mixed solution;

[0039] S4. After the second mixture is precipitated, a light yellow precipitate is obtained. After the light yellow precipitate is filtered, it is placed in an oven at 60° C. and dried for 12 hours to obtain a yellow powdery polyimide powder.

[0040] S5, dissolving the polyimide powder in ethanol and stirring evenly to prepare a polyimide resin solution with a solid content of 40%;

[0041] S6. Place release paper on the platform, cut T300 carbon fiber plain weave fabric of corresponding size and place it on the release paper. The weight of T300 carbon fiber plain weave fabric is 200g / m 2 , the polyimide resin solution is evenly spread on the fabric, and the fabric is baked on a heating platform at 50°C for 2 hours, and then baked at 70°C for 8 hours to obtain a prepreg, the prepreg has a glue content of 35.2%, and the prepreg is cut into corresponding sizes;

[0042] Evenly apply the release agent in the mold, stack 20 prepregs in sequence and place them in the mold. The thickness of the prepreg is 4 mm. Put the mold in a press at 100°C and keep it for 0.5 h. Then keep it at 150°C for 0.5 h. Cover the upper cover of the mold, close the press, continue to heat to 240°C and keep it for 0.5 h. Keep it at 350°C for 20 min. Increase the pressure to 2.5 MPa, continue to heat to 370°C and keep it for 2 h. Keep it at 385°C for 2 h. After curing is completed, cool to room temperature, open the mold and demold, take out the pressed laminate, and obtain a polyimide-based composite material.

[0043] Example 2

[0044] A polyimide-based composite material is prepared by the following steps:

[0045] S1. Add 263 g (3.02 mol) of N,N-dimethylacetamide into a three-necked flask equipped with a mechanical stirring device and a nitrogen introduction device, introduce nitrogen into the three-necked flask, and mechanically stir at -10°C. Add 43.26 g (0.4 mol) of p-phenylenediamine into the three-necked flask, and stir for 2 h to uniformly dissolve the p-phenylenediamine in N,N-dimethylacetamide to obtain a first mixed solution;

[0046] S2, adding 65.44 g (0.3 mol) of pyromellitic anhydride and 39.72 g (0.16 mol) of 4-phenylethynylphthalic anhydride to the first mixed solution in sequence, and stirring at 25° C. for 2 h to obtain a polyamic acid solution;

[0047] S3, adding 190 g of acetic anhydride and 63 g of triethylamine to the polyamic acid solution, stirring at 25° C. for 12 h to obtain a second mixed solution;

[0048] S4. After the second mixture is precipitated, a light yellow precipitate is obtained. After the light yellow precipitate is filtered, it is placed in an oven at 60° C. and dried for 12 hours to obtain a yellow powdery polyimide powder.

[0049] S5, dissolving the polyimide powder in ethanol and stirring evenly to prepare a polyimide resin solution with a solid content of 45%;

[0050] S6. Place release paper on the platform, cut T300 carbon fiber plain weave fabric of corresponding size and place it on the release paper. The weight of T300 carbon fiber plain weave fabric is 200g / m 2 , the polyimide resin solution is evenly spread on the fabric, first baked on a heating platform at 50°C for 2 hours, and then baked at 70°C for 6 hours to obtain a prepreg, the prepreg has a glue content of 35.9%, and the prepreg is cut into corresponding sizes;

[0051] Evenly apply the release agent in the mold, stack 20 prepregs in sequence and place them in the mold. The thickness of the prepreg is 4 mm. Put the mold in a press at 100°C and keep it for 0.5 h. Then keep it at 150°C for 0.5 h. Cover the upper cover of the mold, close the press, continue to heat to 240°C and keep it for 0.5 h. Keep it at 350°C for 20 min. Increase the pressure to 2.5 MPa, continue to heat to 370°C and keep it for 2 h. Keep it at 385°C for 2 h. After curing is completed, cool to room temperature, open the mold and demold, take out the pressed laminate, and obtain a polyimide-based composite material.

[0052] Example 3

[0053] A polyimide-based composite material is prepared by the following steps:

[0054] S1. Add 273 g (2.75 mol) of N-methylpyrrolidone into a three-necked flask equipped with a mechanical stirring device and a nitrogen introduction device, introduce nitrogen into the three-necked flask, and mechanically stir at -10°C. Add 89.67 g (0.4 mol) of 4,4'-diaminodiphenylmethane into the three-necked flask to uniformly dissolve 4,4'-diaminodiphenylmethane in N-methylpyrrolidone to obtain a first mixed solution.

[0055] S2, adding 93.86 g (0.35 mol) of 1,4,5,8-naphthalenetetracarboxylic anhydride and 57.09 g (0.23 mol) of 4-phenylethynylphthalic anhydride to the first mixed solution in sequence, and stirring at 25° C. for 2 h to obtain a polyamic acid solution;

[0056] S3, adding 190 g of acetic anhydride and 63 g of triethylamine to the polyamic acid solution, stirring at 25° C. for 12 h to obtain a second mixed solution;

[0057] S4. After the second mixture is precipitated, a light yellow precipitate is obtained. After the light yellow precipitate is filtered, it is placed in an oven at 60° C. and dried for 12 hours to obtain a yellow powdery polyimide powder.

[0058] S5, dissolving the polyimide powder in ethanol and stirring evenly to prepare a polyimide resin solution with a solid content of 42%;

[0059] S6. Place release paper on the platform, cut T300 carbon fiber plain weave fabric of corresponding size and place it on the release paper. The weight of T300 carbon fiber plain weave fabric is 200g / m 2 , the polyimide resin solution is evenly spread on the fabric, first baked on a heating platform at 50°C for 2 hours, and then baked at 80°C for 6 hours to obtain a prepreg, the prepreg has a glue content of 34.7%, and the prepreg is cut into corresponding sizes;

[0060] Evenly apply the release agent in the mold, stack 20 prepregs in sequence and place them in the mold. The thickness of the prepreg is 4 mm. Put the mold in a press at 100°C and keep it for 0.5 h. Then keep it at 150°C for 0.5 h. Cover the upper cover of the mold, close the press, continue to heat to 240°C and keep it for 0.5 h. Keep it at 350°C for 20 min. Increase the pressure to 2.5 MPa, continue to heat to 370°C and keep it for 2 h. Keep it at 385°C for 2 h. After curing is completed, cool to room temperature, open the mold and demold, take out the pressed laminate, and obtain a polyimide-based composite material.

[0061] Example 4

[0062] A polyimide-based composite material, which is different from Example 1 in that the aromatic diamine monomer is 89.67 g (0.4 mol) of 4,4'-diaminodiphenylmethane.

[0063] Comparative Example

[0064] Comparative Example 1

[0065] S1. Add 245 g (2.81 mol) of N,N-dimethylacetamide into a three-necked flask equipped with a mechanical stirring device and a nitrogen introduction device, introduce nitrogen into the three-necked flask, and mechanically stir at -10°C. Add 32.44 g (0.3 mol) of m-phenylenediamine into the three-necked flask to uniformly dissolve the m-phenylenediamine in N,N-dimethylacetamide to obtain a first mixed solution;

[0066] S2, adding 17.38 g (0.07 mol) of 4-phenylethynylphthalic anhydride to the first mixed solution, stirring at 25° C. for 2 h to obtain a polyamic acid solution;

[0067] S3, adding 143 g of acetic anhydride and 48 g of triethylamine to the polyamic acid solution, stirring at 25° C. for 12 h to obtain a second mixed solution;

[0068] S4. After the second mixture is precipitated, a light yellow precipitate is obtained. After the light yellow precipitate is filtered, it is placed in an oven at 60° C. and dried for 12 hours to obtain a yellow powdery polyimide powder.

[0069] S5, dissolving the polyimide powder in ethanol and stirring evenly to prepare a polyimide resin solution with a solid content of 43.5%;

[0070] S6. Place release paper on the platform, cut T300 carbon fiber plain weave fabric of corresponding size and place it on the release paper. The weight of T300 carbon fiber plain weave fabric is 200g / m 2 , the polyimide resin solution is evenly spread on the fabric, first baked on a heating platform at 50°C for 2 hours, and then baked at 80°C for 5 hours to obtain a prepreg, the prepreg has a glue content of 36.8%, and the prepreg is cut into corresponding sizes;

[0071] Evenly apply the release agent in the mold, stack 20 prepregs in sequence and place them in the mold. The thickness of the prepreg is 4 mm. Put the mold in a press at 100°C and keep it for 0.5 h. Then keep it at 150°C for 0.5 h. Cover the upper cover of the mold, close the press, continue to heat to 240°C and keep it for 0.5 h. Keep it at 350°C for 20 min. Increase the pressure to 2.5 MPa, continue to heat to 370°C and keep it for 2 h. Keep it at 385°C for 2 h. After curing is completed, cool to room temperature, open the mold and demold, take out the pressed laminate, and obtain a polyimide-based composite material.

[0072] Comparative Example 2

[0073] A polyimide-based composite material, the difference from Example 1 is that no chemical imidization treatment is performed.

[0074] Comparative Example 3

[0075] A polyimide-based composite material, which is different from Comparative Example 1 in that the added amount of 4-phenylethynylphthalic anhydride is 0 g.

[0076] Comparative Example 4

[0077] A polyimide-based composite material, the difference from Example 1 is that no nitrogen is introduced into the three-necked flask.

[0078] Performance Testing

[0079] The following performance tests were performed on the polyimide-based composite materials provided in Examples 1-4 and Comparative Examples 1-4 of the present invention:

[0080] Resin melting point: Take a small amount of sample (less than 0.1 mg), grind it and spread it evenly on a glass sheet, then cover it with another glass sheet and place it in an appropriate position on the heating and insulation platform. Then, observe the sample under a microscope while heating and displaying the test temperature. When the temperature is close to the expected melting point, adjust the heating rate until the sample is observed to change from solid to liquid or from glass to highly elastic. The temperature at this time is the melting point.

[0081] Bending strength: composite material specimens of 154.0 mm × 13.0 mm × 4.0 mm were taken respectively, and the bending strength of each specimen was tested according to ASTM D7264.

[0082] Interlaminar shear force: composite material specimens of 24.0 mm × 8.0 mm × 4.0 mm were taken respectively, and the interlaminar shear force of each specimen was tested according to ASTM D2344.

[0083] Glass transition temperature: composite material specimens of 30.0 mm×6.0 mm×4.0 mm were taken respectively, and the glass transition temperature of each specimen was tested according to ASTM D7028-07.

[0084] Three samples were taken for each example and comparative example, and the test results were averaged. The specific test results are shown in Table 2.

[0085] Table 2 Performance results

[0086]

[0087]

[0088] According to Table 1, it can be seen that in Examples 1-4, the prepared resins have good solubility, and the prepared composite materials have excellent mechanical properties and high temperature resistance.

[0089] Compared with Example 1, the mechanical properties of the prepared composite material in Comparative Example 1 are reduced and the high temperature resistance is poor.

[0090] Compared with Example 1, the prepared resin in Comparative Example 3 does not melt below 500° C., which is not conducive to curing and molding, and affects the mechanical properties.

[0091] Finally, it should be noted that the above description is only a preferred example of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A polyimide-based composite material, characterized in that: The raw material composition of the polyimide-based composite material includes, by weight: 5-30 parts of aromatic dianhydride monomer, 4-38 parts of aromatic diamine monomer, 1-10 parts of end-capping agent, 5-30 parts of acetic anhydride, 3-15 parts of triethylamine, and 35-60 parts of solvent.

2. A polyimide-based composite material according to claim 1, characterized in that: The diamine monomer is one or more of 4,4'-diaminodiphenylmethane, m-phenylenediamine, 4,4'-diamino-2,2'-bistrifluoromethylbiphenyl, p-phenylenediamine, and 9,9-bis(4-aminophenyl)fluorene.

3. A polyimide-based composite material according to claim 1, characterized in that: The aromatic dianhydride monomer is selected from one or more of 1,4,5,8-naphthalenetetracarboxylic anhydride, 3,3',4,4'-biphenyltetracarboxylic anhydride, 2,3,3',4'-biphenyltetracarboxylic anhydride, pyromellitic anhydride, hexafluoroisopropylphthalic anhydride or the like.

4. A polyimide-based composite material according to claim 1, characterized in that: The end-capping agent is selected from one or more of 4-phenylethynylphthalic anhydride, 5-norbornene-2,3-dicarboxylic anhydride or the like.

5. A polyimide-based composite material according to claim 1, characterized in that: The solvent is one or more of N,N-dimethylformamide, N,N-dimethylacetamide or N-methylpyrrolidone.

6. A method for preparing a polyimide-based composite material, for preparing the polyimide-based composite material according to any one of claims 1 to 5, characterized in that: The steps include: S1, adding a solvent into a three-necked flask, introducing nitrogen into the three-necked flask and continuously stirring, adding a diamine monomer into the solvent and stirring evenly to obtain a first mixed solution; S2, adding aromatic dianhydride monomer and end-capping agent to the first mixed solution and stirring evenly to obtain a polyamic acid solution; S3, performing imidization treatment on the polyamic acid solution to obtain a second mixed solution; S4, precipitating, filtering and drying the second mixed solution to obtain polyimide powder; S5, adding the polyimide powder into the ethanol solution and stirring evenly to obtain a polyimide resin solution; S6, evenly spreading the polyimide resin solution on the fiber fabric and drying it to obtain a prepreg, and curing the prepreg to obtain a polyimide-based composite material.

7. The method for preparing a polyimide-based composite material according to claim 6, characterized in that: The imidization treatment is specifically: Add acetic anhydride and triethylamine to the polyamic acid solution, and continue stirring at 20-35° C. for 10-12 hours; The solid content of the polyimide resin solution is 10-50%, and the molecular weight of the polyimide is 2200-7500.

8. The method for preparing a polyimide-based composite material according to claim 6, characterized in that: The stirring temperature of the solvent is -10-15°C.

9. The method for preparing a polyimide-based composite material according to claim 6, characterized in that: The amount of the polyimide resin solution laid is 1.2 times the weight of the fiber fabric; The fiber fabric is first baked at 50° C. for 2 hours and then baked at 70° C. for 8 hours to obtain a prepreg; The glue content of the prepreg is 30-40%.

10. The method for preparing a polyimide-based composite material according to claim 6, characterized in that: The prepreg curing molding is specifically as follows: 20 sheets of prepreg were overlapped and laid in the mold and placed in a press at 100°C for 0.5h, then kept at 150°C for 0.5h, and then the mold cover was closed and the press was closed; the temperature was further increased to 240°C for 0.5h, and then to 350°C for 20min, and the press pressure was increased to 2.5MPa; Continue to raise the temperature to 370℃ and keep it for 2h, then keep it at 385℃ for 2h to complete the curing.

Citation Information

Patent Citations

  • Polyimide resin and preparation method thereof

    CN101190968A

  • Thermosetting polyimide resin and preparation method and application thereof

    CN101654518A

  • Polyimide resin and preparation method thereof

    CN102206346A

  • High-dissolubility thermosetting polyimide prepolymer, preparation method and application of high-dissolubility thermosetting polyimide prepolymer

    CN107602856A

  • Low-viscosity high-temperature-resistant thermosetting polyimide resin as well as preparation method and application thereof

    CN112961347A

Cited By

  • Polyimide-based high-temperature hot-melt metal substrate and preparation method thereof

    CN120547757A